2004
DOI: 10.1590/s1413-86702004000300006
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric knowledge about acute viral hepatitis

Abstract: Knowledge about hepatotropic viruses is crucial for pediatricians because of the high prevalence of viral hepatitis during childhood. The multiplicity of hepatotropic viruses, the spectrum of acute and chronic infections, and the sequels of viral hepatitis result in a need for physicians to better understand the clinical and epidemiological context of patients with viral hepatitis, as well as the importance of prevention measures for hepatitis. A descriptive cross-sectional study was made of pediatrician's kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
4
0
4
Order By: Relevance
“…Viral hepatitis is caused by five types of viruses (A, B, C, D and E) that are transmitted differently [ 1 ]. Type A and E are transmitted through food and water [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Viral hepatitis is caused by five types of viruses (A, B, C, D and E) that are transmitted differently [ 1 ]. Type A and E are transmitted through food and water [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that young adults are more susceptible to the infection and that disease severity for this age range is high, healthcare professionals need to be aware of the prevalence of viral hepatitis A in order to identify, evaluate and control epidemics and calculate the impact of vaccination programs. [9][10][11][12] It is worth emphasizing that some studies have showed that vaccination against hepatitis A is capable of preventing disease dissemination during an outbreak, and also of protecting patients' household contacts. 13 In Brazil, there have been few prevalence studies on population samples representative of hepatitis A.…”
Section: Introductionmentioning
confidence: 99%
“… Results of survey of Brazilian physicians on hepatitis B. Adapted with permission from Franca et al [110]. …”
Section: Implications For Managementmentioning
confidence: 99%
“…A survey of 574 paediatricians in Brazil attending a National Congress of Pediatrics in Brasilia revealed that only 4% were able to correctly diagnose hepatitis B, 28% were not familiar with treatment for hepatitis B and only 38% advocated vaccination against hepatitis B to their patients ( Fig. 4) [110].…”
Section: Implications For Managementmentioning
confidence: 99%